Effect of deactivation and reactivation of palladium anode catalyst on performance of direct formic acid fuel cell (DFAFC) - Baik, S. M.; Han, Jonghee; Kim, Jinsoo; Kwon, Yongchai (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In the present study, degradation and recovery in cell performance of direct formic acid fuel cells (DFAFCs) are investigated. For DFAFC tests, palladium (Pd) and platinum (Pt) are used as anode and cathode catalysts, respectively, and are applied to a Nafion membrane by catalyst-coated membrane (CCM) spraying. As multiple repeated DFAFC operations are performed, the cell performance of DFAFC is steadily degraded. This behavior is ascribed to the electrooxidation of Pd into Pd-OH, which occurs between 0.1 and 0.55 V. To investigate the dependency of the cell performance on the Pd-OH and to evaluate how the cell performance is regenerated, cyclic voltammetry (CV) tests are executed. In CV experiments where the voltages applied to the DFAFC single cell are lower than 0.7 V vs. DHE, the cell performance is further deactivated due to continuous production of Pd-OH. Conversely, in CV experiments where the voltage is higher than 0.9 V vs. DHE, cell performance is reactivated due to redox reactions of Pd-OH into Pd-O and Pd-O into Pd. ATR-FTIR and XPS are used to confirm the transformations of Pd. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: INFRARED-ABSORPTION SPECTROSCOPY; GOLD ELECTRODES; CARBON-MONOXIDE; ELECTROOXIDATION; METHANOL; PD; NANOPARTICLES; IMPEDANCE; OXIDATION; OXYGEN